Survivin induces defects in apoptosis in eosinophils in intestine with food allergy. Issue 4 (May 2019) - Gao, Han; Feng, Bai-Sui; Liu, Jiang-Qi; Mo, Li-Hua; Geng, Xiao-Rui; Xiao, Yuan; Zhang, Yuan-Yi; Hong, Jing-Yi; Liu, Zhan-ju; Liu, Zhi-Gang; Feng, Yisheng; Yang, Ping-Chang
Survivin is an anti-apoptosis protein that may be associated with the development of eosinophilia; the latter is associated with the pathogenesis of many immune disorders. Here we report that less apoptotic eosinophils (Eos) were induced in those isolated from mice suffering from food allergy (FA) than those from naive mice after treating with cisplatin in vitro . Exposure to cisplatin induced more Fas ligand (FasL) expression in Eos isolated from naive mice than in those of FA mouse. Survivin was detected in the intestinal tissue extracts in much higher amounts in the FA group than in the naive group. Immunohistochemistry showed that epithelial cells were the major source of survivin in the intestine. Exposure to IL-4 or IL-13 up-regulated the expression of survivin in intestinal epithelial cells. Survivin interfered with the expression of FasL in Eos. Inhibition of survivin attenuated the eosinophilia-related inflammation in the intestine. In conclusion, intestinal epithelial cell-produced survivin induced defects in apoptosis in Eos to contribute to eosinophilia in the intestine. Inhibition of survivin can suppress the eosinophilia-related intestinal inflammation. The data suggest that survivin may be a novel target for the treatment of FA.